2017
DOI: 10.4088/jcp.16m10762
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Markers and Brain-Derived Neurotrophic Factor as Potential Bridges Linking Bipolar Disorder and Cardiovascular Risk Among Adolescents

Abstract: This study found evidence of increased inflammation among adolescents with BD. While present findings suggest a potential interplay between symptomatic status, biomarkers, and atherosclerosis proxies, there were no significant differences in cIMT or flow-mediated dilation in adolescents with BD compared to HCs. This may indicate that there is potential opportunity for CVD prevention strategies in adolescents with BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…241 The second study (40 BD patients and 20 HCs) found elevated IL-6 and TNF-α levels among adolescents with PBD. 242 …”
Section: | Peripheral Biomarkersmentioning
confidence: 99%
“…241 The second study (40 BD patients and 20 HCs) found elevated IL-6 and TNF-α levels among adolescents with PBD. 242 …”
Section: | Peripheral Biomarkersmentioning
confidence: 99%
“…Similarly, Soeiro-de Souza and colleagues described that patients with recurrent episodes showed increased oxidative and inflammatory markers, which were related to the number of manic episodes ( 101 ). Further, increased inflammation, increased oxidative stress and reduced telomere length have been suggested as possible mechanistic links between psychiatric diseases like bipolar disorder and other systemic diseases, such as endocrine or cardiovascular diseases ( 102 105 ). Hence, the identification of a deregulation on those pathways related to both psychiatric and somatic diseases may have therapeutic implications ( 106 ).…”
Section: From Staging To Precision Staging Modelsmentioning
confidence: 99%
“…BDNF is considered a biomarker for mental disorders such as bipolar disorder; as these patients have a high risk of developing cardiovascular disease, BDNF could be a link between the two diseases (176). Manni and colleagues demonstrated that serum BDNF was reduced in patients with acute coronary disease (ACD), hence, this neurotrophin may be implicated in the pathogenesis of cardiovascular disease (177); low serum BDNF were also found in patients with ACD during an oral glucose tolerance test (OGTT) (178).…”
Section: Brain- Neuron- Glial Cell Line-derived Neurotrophic Factormentioning
confidence: 99%